Research Review of Thermal Ablation in the Treatment of Papillary Thyroid Carcinoma - Ou, Di; Chen, Chen; Jiang, Tian; Xu, Dong (Frontiers in Oncology, 2022)
Abstract: Background: Minimally invasive treatment of thyroid tumors has become increasingly common, but has mainly focused on benign thyroid tumors, whereas thermal ablation of thyroid cancer remains controversial. Clinical studies analyzing the efficacy of thermal ablation of papillary thyroid cancer (PTC) have been conducted in several countries to verify its safety. Here, we screened and reviewed recent studies on the efficacy and safety of thermal ablation of PTC as well as psychological assessment, patient prognosis, recurrence, and factors affecting ablation. Summary: The most significant controversy surrounding ablative treatment of PTC centers on its effectiveness and safety, and >40 studies have been conducted to address this issue. The studies include papillary thyroid microcarcinoma (PTMC) and non-PTMC, single PTC and multiple PTC, and controlled studies of ablative therapy and surgical treatment. In general, ablation techniques can be carefully performed and promoted under certain conditions and with active follow-up of postoperative patients. Ablation is a promising alternative treatment especially in patients who are inoperable. Conclusions: Clinical studies on PTC ablation have provided new perspectives on local treatment. However, because PTC grows very slowly, it is an indolent tumor; therefore, studies with larger sample sizes and extended post-procedure follow-ups are necessary to confirm the investigators’ hypotheses.